2008 IEEE International Symposium on Industrial Electronics 2008
DOI: 10.1109/isie.2008.4677206
|View full text |Cite
|
Sign up to set email alerts
|

Impact of power converter current ripple on the durability of a fuel cell stack

Abstract: The durability and performance of Polymer Electrolyte Membrane Fuel Cell (PEMFC) have a major impact on the most important challenges facing fuel cell commercialization including final cost, mass production, system integration, functionality and reliability. This work is supported by French Government via an ANR' project (PAN'H) named SPACT80. The global objective is to develop and validate the use of a fuel cell based power system for heavy-duty vehicles (dedicated to railway applications or hybrid electrical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
39
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(39 citation statements)
references
References 9 publications
0
39
0
Order By: Relevance
“…The aging under a constant current of 70A for FC2 and under small variations at high frequency (5kHz) around 70A for FC1 are observed during 1000 hours. More details about the stacks and the experiments can be found in [38,39]. Eight characterizations are carried out throughout the aging (polarization curve and electrochemical impedance spectroscopy) leading to voltage disturbances, peaks are visible (Fig 6).…”
Section: Available Data Presentationmentioning
confidence: 99%
“…The aging under a constant current of 70A for FC2 and under small variations at high frequency (5kHz) around 70A for FC1 are observed during 1000 hours. More details about the stacks and the experiments can be found in [38,39]. Eight characterizations are carried out throughout the aging (polarization curve and electrochemical impedance spectroscopy) leading to voltage disturbances, peaks are visible (Fig 6).…”
Section: Available Data Presentationmentioning
confidence: 99%
“…It has been suggested that current ripple can increase the losses and fuel waste thus decreasing the cell efficiency [20,22], can lead the cell to operate in dangerous conditions in case of too low reactant concentration [19] and finally it might decrease the fuel cell durability [19,21,23]. For these reasons recent studies have been focused on ripple mitigation [24e27].…”
Section: Introductionmentioning
confidence: 99%
“…First of all, a decrease of the PEMFC polarization curve from 5 to 10% with a sinusoidal current ripple at 1 kHz and a peak‐to‐peak value of 20% of the FC average current (i.e. 250 A) . The evolution of PEMFC stack voltage both the reference aging test and the dynamic test is illustrated in Figure .…”
Section: Reliability and Current Ripple Issues In Fcev Applicationsmentioning
confidence: 96%